ENVIRONMENTAL POLLUTION RISK ANALYSIS AND MANAGEMENT IN TEXTILE INDUSTRY: A PREVENTIVE MECHANISM - Venkatesh Jaganathan; Priyesh Cherurveettil; Aarthy Chellasamy; M.S. Premapriya (European Scientific Journal, ESJ, 2014)
The textile industry is major contributor in many nations in terms of economies and employment. The small and large scale operations in this textile sector though contribute much to the economy also cause hazardous effect to environment. The textile manufacturing processes involve large consumption of water, energy and various chemicals which will generate waste at the end or as a by-product. The major problem with regard to water usage is the untreated effluents which are discharged directly into nearby water bodies. Not only water bodies cause environmental damage other factors like gas emissions, excessive odors etc are also considered to be pollutants. Environmental pollution risk analysis and risk management in textile industry is vital in order to prevent chemical disaster which may lead to terrible results. It is also important to maintain production level at the same time. This paper aims to identify and analyze the pollution due to water and air in a textile industry and steps to reduce the risk which arises due to pollution.